Assessment of various forms of cellulose-based Luffa cylindrica (mat, flakes and powder) reinforced polydimethylsiloxane composites for oil sorption and organic solvents absorption - Gundu S.; Sahi A.K.; Kumari P.; Vishwakarma N.K.; Mahto S.K. (My University, 2025)
Oil spillage has damaged public health noticeably and contributed to significant environmental deterioration. As a result, a significant amount of effort has been spent on investigating and developing the sorbent materials capable of separating oil from water. Thus, the sorbent materials that could be effective particularly in oil spill disposal and resolve such environmental issue remain to be explored. We have proposed luffa cylindrica (LC)-polydimethylsiloxane (PDMS) composite forms to remove the oil and organic components that might be hazardous to aquatic organisms. The scaffolds were fabricated using hand lay-up method with various forms of luffa cylindrica i.e., LC mat, flakes and powder. Various characterizations such as scanning electron microscopy (SEM), atomic force microscopy (AFM), thermogravimetric analysis (TGA), effective porosity, surface wettability, mechanical stability, cytotoxicity and sorption behavior with respect to oil, phosphate buffer saline (PBS) and few organic solvents were performed. The results showed that the scaffold in combination with P-L flakes was highly effective in eradicating oil spills and removing harmful components of crude oil. Scaffolds composed of P-L mat, P-L flakes, P-L powder, and PDMS (P) exhibited oil absorption efficacy around 16.09 ± 4.62 %, 24.49 ± 3.55 %, 15.52 ± 2.67 % and 5.52 ± 1.44 %, respectively. We anticipate that the proposed scaffolds have the tremendous potential to provide a solution to this significant environmental remediation issue and to serve as a cost-effective method for removing oil spills and hazardous crude oil components. © 2023